Incidence and associated factors of posterior capsule opacification in pseudophakic patients at Cipto Mangunkusumo Hospital (Faculty of Medicine Universitas Indonesia, 2015)
Background: Posterior capsule opacification (PCO) is the most common postoperative consequence of cataract surgery which may cause visual acuity reduction, yet the incidence in Indonesia has not been reported. The objectives of this study were to evaluate three years cumulative incidence of PCO and factors associated with PCO formation at Cipto Mangunkusumo Hospital, Jakarta. Methods: This was a retrospective descriptive study on patients with uneventful senile cataract surgery during year 2010. All related data were retrieved from medical records in year 2013, which included patient demographics, type of surgery, intraocular lens (IOL) characteristics (material, optic edge design and diameter). Moreover, time to first PCO diagnosis (month), and best corrected visual acuity (BCVA) pre-operatively, at time PCO was diagnosed and two weeks after Neodymium-doped yttrium aluminum garnet (Nd:YAG) laser were noted (decimal). Results: A total of 578 eyes (485 patients) were involved in this study. Three years cumulative incidence of the PCO was 8.82% (51 eyes). Phacoemulsification surgery was performed in 496 (85.8%) eyes. The median time to PCO diagnosis was 21 months (range 1 to 34 months), mean of BCVA was 0.50 ± 0.26. Age (<65 and >65 years old) was not associated to PCO. Higher incidence of PCO was found in patients using hydrophilic acrylic IOL (10.7%) than in hydrophobic acrylic (6.2%). After Nd:YAG laser was performed, BCVA was improved to 1.00. Conclusion: Three years cumulative incidence of PCO was 8.82% and there was no defined factor related to PCO formation, but higher percentage of PCO occured in patients using hydrophilic acrylic IOL than in hydrophobic acrylic.